PEMETAAN INDEKS BAHAYA DAN KERENTANAN BENCANA LETUSAN GUNUNGAPI DI KABUPATEN BLITAR (STUDI KASUS KECAMATAN GANDUSARI) - Abdullah Ali; Umi Sa'adah; Punjung Aziz Satria (Jurnal Manajemen Bencana (JMB), 2021)
Mount Kelud is a strato-volcanic type with explosive characteristics of a large explosion. Until now, Mount Kelud is classified as active with an eruption period of about 5-25 years. Historically, the highest eruption of Mount Kelud occurred in 1990 which reached 5 on the VEI scale and submerged Gandusari District with pyroclastic material. Gandusari sub-district is located 0-7 km from the crater, making this sub-district has a high hazard index against volcanic eruptions. This study aims to map the hazard and vulnerability index of the eruption of Mount Kelud in Gandusari District as one of the mitigation efforts. The hazard index mapping was carried out by digitizing the Kelud Volcanic Eruption Hazard Area (KRB) map published by PVMBG, while the vulnerability index was calculated using spatial data from the Blitar Regency Public Works and Public Housing (PUPR) and non-spatial data from the Central Statistics Agency. (BPS) Blitar Regency. The mapping results show that areas with a high hazard index are located in the Kelurahan Gandusari, Ngaringan, Soso, Tulungrejo, and Krisik. Meanwhile, areas with a high vulnerability index are located in Ngaringan, Sokosewu, Butun, Sumbung, and Semen Villages.